Three-dimensional bio-printed constructs consisting of human umbilical-derived mesenchymal stem cells promote cell viability, proliferation, and differentiation in vitro - Tao, Qingxia; Wu, Cuiying; Li, Xinda; Chen, Wenjin; Sun, Kai; Zhang, Peng; Yang, Zhijun; Liu, Ning; Xu, Ruxiang; Xu, Tao; Wang, Chong (Cellular and Molecular Biology, 2020)
The aim of this study was to investigate the effect of three-dimensional (3D) bio-printed constructs consisting of human umbilical-derived mesenchymal stem cells (HUMSCs) on cell viability, proliferation and differentiation in vitro. Functional 3D bio-printed microspheres consisting of HUMSCs were constructed using electrostatic inkjet technique. The parameters used for the synthesis of 3D bio-printed tissue constructs were first optimized. The viability, proliferation and differentiation of 3D cultured HUMSCs were assessed. The results of scanning electron microscopy (SEM) showed that isolated HUMSCs exhibited fibroblast-like spindle adherent growth. The optimized printing parameters were 6 kV voltage, 10 mL/h flow, 15 cm receiving height, and alginate: water ratio of 1:1 mixed at 37 °C. Compared with 2D cultured HUMSCs, the 3D cultured HUMSCs have better viability, proliferation and differentiation ability. The results obtained in this study indicate that 3D bio-printed tissue constructs promote HUMSC viability, proliferation, and neural differentiation in vitro.